Screening of Padina boergesenii for pharmacological activities - Mahendran, Nirmala; Rajendran, Priya; Kandasamy, Sasikumar; Kuppannan, Gobianand; Poyil, Muhammad Musthafa; Arthanari, Malarvizhi (Current Botany, 2023)
Padina boergesenii is a distinctive small brown algae with rounded fronds growing to a length and diameter of 04 to 06 cm (1.6 to 2.4 in). P. boergesenii is widely present in the shallow water of tropical, subtropical and warm temperate areas. The present study aimed to investigate the anti-bacterial, anti-biofilm, antioxidant, anti-inflammatory and cytotoxicity activities of crude ethyl acetate extract of P. boergesenii. Anti-bacterial activity of crude ethyl acetate extract of P. boergesenii against Gram-positive and Gram-negative bacteria was determined using the well diffusion method. MIC of P. boergesenii against biofilm was carried out by the Resazurin method. Antioxidant potential was assessed by DPPH, FRAP, and the Hydrogen peroxide scavenging method. The anti-inflammatory activity was investigated using the albumin denaturation and heat-induced hemolysis method. Cytotoxicity activity of P. boergesenii against cell line L929 was analyzed by MTT assay. The maximum zone of inhibition obtained was 23 mm for Staphylococcus aureus, followed by 21 mm for Escherichia coli. Biofilm of Enterococcus faecalis showed higher resistance (MIC= 25.00±00.00 mg/mL). Biofilm of Acinetobacter baumannii was found to be most susceptible (MIC= 06.25±00.00 mg/mL). The IC50 value for the crude ethyl acetate extract P. boergesenii was 155.5 μg/mL for the DPPH method, 1567.18 μg/mL for the FRAP method, and 3098.27 μg/mL for the H2O2 method. The results of in vitro anti-inflammatory studies exhibited IC50= 122.33 μg/mL and 2522.40 μg/mL for albumin denaturation assay and heat-induced hemolysis method respectively. The crude ethyl acetate extract of P. boergesenii showed cytotoxicity against the growth of the L929 cell line. The present study suggested that the crude ethyl acetate extract P. boergesenii has potent antibacterial, anti-biofilm, antioxidant, anti-inflammatory and cytotoxicity activities. The bioactive components present in the P. boergesenii extract can be a promising source for pharmaceuticals.